Faktor Penentu Earning Per Share Perusahaan Properti dan Real Estate yang Terdaftar dalam Indeks Saham Syariah Indonesia - Gayatri Aisyah Ardinindya; Tjetjep Djuwarsa (Journal of Islamic Economics and Business, 2021)
In conducting this study, to determine the effect of the Current Ratio, Debt to Assets Ratio, Return on Assets to the Earning Per Share of property and real estate companies listed in ISSI. The sample in this study consisted of 12 property and real estate companies registered with ISSI. The data used was obtained from the official website of the Indonesia Stock Exchange, as well as the company's official website. The analytical method used is the panel data regression method using EViews 10 Software. The results obtained from this research are; CR partially positive and insignificant effect on EPS, DAR partially positive and not significant effect on EPS, ROA partially positive and significant effect on EPS, CR, DAR, and ROA simultaneously positive and significant effect on EPS.